The infiltration of Western methodologies into Arabic critical studies – The works of Taha Hussein as a model - zelafi, brahim (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract The present paper aims at shedding light on the outlets from which Western approaches infiltrated into Arab critical studies. This was during the period of intellectual weakness experienced by the Arab nation, especially during the colonial invasion of the Arab lands, which was able to influence the thought of a large group of Arab thinkers who studied in its schools, and familiarised themselves with the Western culture.They took the writings of Western writers as reliable sources for quoting the correct information, and they adopted their methods to study the ancient and modern Arab heritage.Thiscwas the reason why the impact of Western thought was obvious in the writings of some Arab writers who were taught by these Western thinkers, whether in universities or institutes inside the Arab world or in European universities. Among these Arab thinkers was the Egyptian writer and critic Taha Hussein, whose extremely writings were influenced by the Western intellectual model.